2016
DOI: 10.1177/0022466916656174
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Teacher Sorting in Secondary Special Education and Alternative Schools

Abstract: This study provides nationally representative information about the qualifications and preparation of secondary content and special education teachers in special education and alternative school settings, as compared with teachers in regular schools. Findings demonstrate that a statistically significant relationship did not exist between school types and many teacher inputs. However, a relationship between special education preparation and setting did exist among secondary content teachers. Moreover, results h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 38 publications
(80 reference statements)
4
27
0
Order By: Relevance
“…Teacher turnover has significant detrimental effects on schools and students (Feng & Sass, 2017;Milanowski & Odden, 2007;Ronfeldt, Loeb, & Wyckoff, 2013). Turnover contributes to inequities in the distribution of effective teachers across schools as teachers move from low-to high-resource schools (Clotfelter, Ladd, & Vigdor, 2006;Feng & Sass, 2017;Lankford, Loeb, & Wyckoff, 2002;Mason-Williams, 2015;Mason-Williams & Gagnon, 2017), and creates a financial burden for schools and districts who must recruit new teachers to fill vacant positions (Milanowski & Odden, 2007). Turnover negatively affects student academic outcomes by disrupting instructional cohesion (Ronfeldt et al, 2013;Hanushek, Rivkin, & Schiman, 2016) and poses a significant challenge to the continuous implementation of effective educational programs (McLeskey & Billingsley, 2008).…”
Section: The Association Between Teaching Students With Disabilities mentioning
confidence: 99%
See 2 more Smart Citations
“…Teacher turnover has significant detrimental effects on schools and students (Feng & Sass, 2017;Milanowski & Odden, 2007;Ronfeldt, Loeb, & Wyckoff, 2013). Turnover contributes to inequities in the distribution of effective teachers across schools as teachers move from low-to high-resource schools (Clotfelter, Ladd, & Vigdor, 2006;Feng & Sass, 2017;Lankford, Loeb, & Wyckoff, 2002;Mason-Williams, 2015;Mason-Williams & Gagnon, 2017), and creates a financial burden for schools and districts who must recruit new teachers to fill vacant positions (Milanowski & Odden, 2007). Turnover negatively affects student academic outcomes by disrupting instructional cohesion (Ronfeldt et al, 2013;Hanushek, Rivkin, & Schiman, 2016) and poses a significant challenge to the continuous implementation of effective educational programs (McLeskey & Billingsley, 2008).…”
Section: The Association Between Teaching Students With Disabilities mentioning
confidence: 99%
“…Studies of out-of-field placement, when a teacher is assigned classes in an area in which they are not certified or trained, also suggest the importance of training and certification to attenuate to turnover (Donaldson & Johnson, 2010;Ingersoll, 1999). Preparation or skill, STUDENTS WITH DISABILITIES AND TURNOVER 6 commonly indicated in the existing literature by certification (e.g., Feng & Sass, 2013;Gottfried et al, 2016;Mason-Williams, 2015;Mason-Williams & Gagnon, 2017), could play an important role in teacher turnover especially in light of the varied skills indicated by special education and general education certification.…”
Section: Preparation As a Moderatormentioning
confidence: 99%
See 1 more Smart Citation
“…Research in both special and general education on teacher sorting has focused almost exclusively on regular school settings, ignoring the extent to which teachers may unevenly distribute among special education and alternative school settings. To fill this gap in the research literature, Mason-Williams and Gagnon (2017) demonstrated that secondary alternative and special education schools disproportionately employed less-qualified teachers than neighborhood schools. Using data from the 2007–2008 SASS (SASS:08) dataset, the researchers found that, compared to neighborhood schools, teachers in special education and alternative secondary schools were significantly less likely to have preparation in academic content areas, while content area teachers in secondary exclusionary schools more often lacked special education preparation.…”
Section: Teacher Sorting In Special Educationmentioning
confidence: 99%
“…Their study, in combination with smaller studies demonstrating the effects of preparation on instructional quality (e.g., Nougaret, Scruggs, & Mastropieri, 2005), provides justification for ensuring all students with disabilities have access to well-qualified special educators. Yet estimates consistently indicate that many schools continue to rely heavily on special educators who lack basic qualifications, such as full certification or a degree in special education, teaching experience, or coursework in teaching methods (Fall & Billingsley, 2011; Mason-Williams, 2015; Mason-Williams & Gagnon, 2017). Apparently, although a sufficient knowledge base exists as to how to intervene to raise the achievement of students with disabilities, we lack qualified individuals capable of applying those interventions in classrooms.…”
mentioning
confidence: 99%